ANALISIS PENGARUH IMPOR, JUMLAH UANG BEREDAR, SUKU BUNGA, HARGA KOMODITAS TERHADAP INFLASI DI INDONESIA TAHUN 2020-2023 - Roviq, Ahmad; Ashari, Muhammad Zidanaim; Hanafi, Muhammad Roichan; Nugroho, Ali Dwi; Dimyati, Bintis Tianatud (Investama : Jurnal Ekonomi dan Bisnis, 2025)
Inflation is a condition in which there is a general and continuous increase in the price of goods and services in an economy, resulting in a decrease in people's purchasing power as measured using the Consumer Price Index (CPI) and the Producer Price Index (CPI), which reflect price changes in various sectors. In economic conditions, inflation can be influenced by several factors such as imports, money supply, interest rates, and commodity prices by obtaining reference data from official websites such as the Central Statistics Agency (BPS) which focuses on monthly data from 2020 to 2023. The author's research was carried out using secondary data with multiple linear regression analysis methods. Based on the results of the study, it is known that: (1) the results of statistical tests show that imports partially have a significant effect on the dependent variable of Inflation, this is because the increase in imports tends to reduce inflationary pressure, because imports help balance the domestic inventory of goods. (2) The results of the statistical test show that the money supply partially does not have a significant effect on the inflation variable, meaning that an increase or decrease in the amount of money in circulation in 2020 to 2023 does not necessarily cause inflation, so it can be concluded that there are factors that affect inflation more during that period, such as mobility restrictions due to the pandemic. (3) The results of the statistical test show that interest rates do not have a significant effect on inflation variables This occurs because in the 2020-2023 period, inflation is more influenced by external factors such as the global supply crisis, import inflation, and expansionary fiscal policy as a form of pandemic countermeasures. (4) The results of statistical tests show that the existence of commodity prices has no effect on inflation, meaning that when commodity prices increase, inflation tends to decrease with the possibility of the influence of insignificant commodity prices individually caused by other factors that are more dominant to affect inflation such as a decrease in aggregate demand.